Physical properties evolution and microscopic mechanisms of granite modified by thermal and chemical stimulation - Jiliang Pan; Xun Xi; Xu Wu; Qifeng Guo; Fenhua Ren; Meifeng Cai (Case Studies in Thermal Engineering, 2023)
Geothermal reservoirs are reformed by thermal and chemical stimulation combined with hydrofracture, which is more effective in forming artificial fracture networks. It is critical for the efficient development of geothermal resources to understand the changes in the physical properties of hot dry rock (HDR) during reservoir reconstruction. Granite samples subjected to thermal stimulation at different temperatures are conducted with static immersion tests of different chemical solutions for 48 days to study the effects of thermal and chemical stimulation on HDR. P-wave velocities, porosity, and thermophysical parameters (thermal conductivity and thermal diffusivity) of thermal-chemical-modified granite are measured by ultrasonic testing (UT), nuclear magnetic resonance (NMR), and transient plane source (TPS), respectively. The effects of different heat-treatment temperatures and chemical solutions on the physical properties of granites are studied. After that, the functional relationship between the physical parameters and heat-treatment temperature is quantitatively characterized, and the correlation between the different physical parameters is analyzed. The thermal and chemical damage mechanisms of granite are revealed from its physical properties, pore structures, and mineral compositions. Results showed that thermal stimulation is more likely to change the physical properties of granites than chemical stimulation, and the physical properties significantly changed at a temperature threshold of 300°C. The mass of thermal-chemical-modified granites decreased with the increased heat-treatment temperature; the P-wave velocity decreased linearly; the porosity increased nonlinearly; the thermal conductivity decreased exponentially; the thermal diffusivity decreased linearly. Porosity increased with the decreased P-wave velocity, which presented a nonlinear relationship. The thermophysical parameters are negatively correlated with porosity and positively correlated with the P-wave velocity. The acid solution stimulation further caused the decreased P-wave velocity and increased porosity of heat-treated granite samples, which reduced the thermal conductivity of samples. However, the alkaline solution stimulation is the opposite. The pore structure development and phase transformation are the essential reasons for the changes in the physical properties of thermal-chemical-modified granites.